Acute Acalculous Cholecystitis: Think of Hepatitis A Infection and Do Not Underestimate Pain. Issue 6 (26th June 2022) - Cortellazzo Wiel, Luisa; Spezzacatene, Anita; Gortani, Giulia; Saccari, Alessia; Taddio, Andrea; Barbi, Egidio
Abstract: A 14-year-old adolescent girl presented with severe abdominal pain, tenderness, and guarding in the right upper quadrant associated with nonbilious vomiting, scleral icterus, and fever. Laboratory tests were consistent with acute hepatitis A virus–related cholestatic hepatitis. A point-of-care ultrasound showed mild gallbladder wall thickening with increased color Doppler flow and pericholecystic fluid collection, in the absence of gallstones or biliary ducts dilatation, thus suggesting acute acalculous cholecystitis. Both the clinical symptoms and the point-of-care ultrasound findings completely resolved within 1 week after admission with conservative treatment.